Zygomaticomaxillary suture maturation: Part II—The influence of sutural maturation on the response to maxillary protraction. (29th June 2017) - Angelieri, F.; Ruellas, A. C.; Yatabe, M. S.; Cevidanes, L. H. S.; Franchi, L.; Toyama‐Hino, C.; De Clerck, H. J.; Nguyen, T.; McNamara, J. A.
Structured Abstract: Objective: To evaluate the influence of the maturational stages of zygomaticomaxillary sutures (ZMS) on the response to maxillary protraction. Subjects and Methods: A total of 40 Class III patients were treated retrospectively with either a combination of rapid maxillary expansion and facial mask (RME/FM) or bone‐anchored maxillary protraction (BAMP). The RME/FM group consisted of 18 patients (mean age 8.3 years), while the BAMP group was comprised of 22 patients (mean age 11.8 years). The initial CBCT images (T1) of the ZMSs were classified blindly. 3D models from CBCT images at the start and at the end of orthopaedic treatment were registered on the anterior cranial base, and corresponding structures were measured on colour‐coded maps and semitransparent overlays. The amounts of protraction of the maxilla, zygoma, orbitale and maxillary first molars for both groups were analysed with two‐way ANOVA with Holm‐Sidak post hoc test for multiple comparisons. Results: A significant association was found between the early maturation stages of the ZMSs and the amount of maxillary protraction, regardless of the protraction method used. Class III patients with ZMS stages A and B showed greater maxillary protraction than patients at stage C. Conclusion: The maturational stages of ZMS are associated with the response maxillary protraction.